Precarização do trabalho e adoecimento: a realidade de professores de uma rede de educação num município ao norte do Rio Grande do Sul - Junges Junior, Mario Luiz (2020)
The research that resulted in this dissertation deals with a theme that has been gaining more and more relevance in the academic and social sphere. Studies that report working conditions and their relationships with workers' illness grow in Brazil, especially since the 1980s with the expansion of mental health assessments. In previous decades, the focus of investigations on workers' health was directed to occupational accidents and diseases of the body, focusing on the activity of the worker as responsible for the illness. Considering the changes that have occurred in the world of work in recent decades, we aim with this research to evaluate how the restructuring of capitalism in its neoliberal phase contributes to the illness of teachers. Specific objectives are to identify the particularities of the world of work in neoliberal society; understand the work as a generator of illness and analyze the reality of the teacher's illness in a network of a municipality north of Rio Grande do Sul. For this, a bibliographic and documentary research was carried out, with a qualitative approach, having as research universe the municipal education network. The bibliographic base had the contribution of authors such as Marx, Antunes, Byung-Han and Sennett. The documentary data were analyzed with Bardin's support, through a content analysis, which allows the description of the content of the communications and analyzes what can be announced after the treatment of these contents. In this investigated context, the influence of the neoliberal capitalist mode of production on the interfaces between work and illness is evident. From this perspective, the understanding of teacher illness can be shifted from a logic strictly focused on classroom activity, as an isolated generating factor of illness, to think of this phenomenon as a result of social organization. Based on the data made available in dialogue with the bibliographic production, it is possible to conclude that the neoliberal rationality guiding the production relations increasingly enters the school that has been used for the propagation of the ideas of the competitive and winning neoliberal subject, as well as experiencing the precariousness of working conditions, making the teaching activity more intense, making flexibilization and individualizing the responsibilities for school success or failure and, consequently, playing numerous attributions to teachers, factors that aggravate the teacher's illness.